TEACHER AND STUDENT PERCEPTIONS OF THE DEVELOPMENT OF SOCIAL STUDIES LEARNING MEDIA BASED ON STOP MOTION INFOGRAPHICS ON SOCIAL MOBILITY MATERIALS - Nurhayati, Dwi Astuti Wahyu; Agustina, Lina Nurlaili (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Media development is a step and process in making or perfecting a media in the learning process is that learning is more effective, efficient and able to achieve the learning objectives to be achieved. This study describes how teachers and students perceive the learning media in the form of stop motion infographic animations. It is the perception of students here that also determines the success or failure of learning by using stop motion infographic animation learning media and to find out whether or not stop motion infographic animation learning media is appropriate, learning media can support understanding and increase student interest in learning so that learning does not seem monotonous. This study used the Research and Development research method with a research model according to Borg and Gall. The techniques used in the research are questionnaires, observations, post-test and interviews. The main object of this research is class VIII students at SMPN 2 Kademangan. The gaining of media validation test result with an average percentage of 88.6% is valid category, then material validation result was 93.3% and the teacher validation test result was got 84.2%, it showed the valid category, it meant that it fulfilled the criteria of practicality with the gained of 87.5% as pupils ‘completeness score; then analysis of pupils’ activity observation portrayed a percentage of 15.6% it seemed the media was effective by considering the result of hypothesis testing using Paires Sample Test (sig. 2-tailed, 0.000 <0.05. the result of sig 0.000= 0.05). It is also seen form the average value between the pre-test and post test, those are the pretest score 70.1563 is lower then the posttest score of 79.375, it meant that the media was supposed effective to be employed to enhance the pupils’ interest.